THE SCOURING OF BINAHONG LEAVES ACCELERATES THE HEALING OF BURNS ON WHITE RATS - Airlangga, Komang Sri Gilang; Gorda, I Wayan; Dada, I Ketut Anom; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2019)
Burns wound is a condition where the skin tissue damage due to skin contact by the heat source such as electricity shock, chemicals irritation, fire and radiation. Research on Binahong (Anredera Cordifolia (Tenore) Steenis) has been conducted by applying leaf crush Binahong plant on the rat skin surface (Rattus norvegicus). The result is that Binahong plany can heal burns. It proven that on the examination of macroscopic microscopic of the white rats skin can shorter duration of inflammation by fasten collagen density epithelialization.[11: Research results were statistically analyzed with the help of tools SPSS for windows 17 conducted using The Randomize Posttest Only Control Group Design. Thirty-two (32) female white rats weight 150-200 gram were divided into two treatments in which each treatment consisted of 16 rats.  results were statistically analyzed with the help of tools SPSS for windows 17.  Results of the study are: 1. Binahong leaves binahong affecting the healing of burns on rats by accelerating the speed of skin epithelialization process. 2. The research result can be used for treatment of skin burn. And suggesting that Binahong can be used particularly in remote area where lack of medicine access.